2010
DOI: 10.1021/jf904139e
|View full text |Cite
|
Sign up to set email alerts
|

Agonists and Antagonists of Antennal Responses of Gypsy Moth (Lymantria dispar) to the Pheromone (+)-Disparlure and Other Odorants

Abstract: Insects use the sense of smell to guide many behaviors that are important for their survival. The gypsy moth uses a pheromone to bring females and males together over long distances. Male moth antennae are equipped with innervated sensory hairs that selectively respond to pheromone components and other odors. Host plant odors, in particular, are detected by moths and sometimes cause an enhancement of the antennal and behavioral responses of the moths to their pheromone. Inspired by naturally occurring agonists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 69 publications
3
25
1
Order By: Relevance
“…This long-term inhibition appeared stronger than the short-term effect for cy { 2,2 } and HCO-2-169, but it was eliminated in a fourth stimulation with bee headspace that was applied after stimulation with air (data not shown). A similar result has been obtained with gypsy moths treated with the sex pheromone, (+)-disparlure, and a blend 3c { 1-5,3 } [19]: the long-term inhibition was reversible, and the response to pure pheromone returned to normal 4–5 puffs after the mixed puff (pheromone + 3c { 1-5,3 }). In the present study, there were different structure-activity relationships for the short-term and long-term effects.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…This long-term inhibition appeared stronger than the short-term effect for cy { 2,2 } and HCO-2-169, but it was eliminated in a fourth stimulation with bee headspace that was applied after stimulation with air (data not shown). A similar result has been obtained with gypsy moths treated with the sex pheromone, (+)-disparlure, and a blend 3c { 1-5,3 } [19]: the long-term inhibition was reversible, and the response to pure pheromone returned to normal 4–5 puffs after the mixed puff (pheromone + 3c { 1-5,3 }). In the present study, there were different structure-activity relationships for the short-term and long-term effects.…”
Section: Resultssupporting
confidence: 78%
“…The effect of the compounds was evaluated relative to the response to the “positive stimulus” before the exposure to the tested compound. According to previous studies [19], [20], two kinds of effect were evaluated: the effect that occurred in the presence of the compound termed “short term effect”, and the effect following the administration of the compound but not in its presence termed “long term effect”. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a few examples of synergistic effects of plant odours added to sex pheromone have been reported (Ochieng et al, 2002;Plettner and Gries, 2010), the most frequently observed effect consisted of a suppression of the pheromonal response when a plant odour is added (Schneider et al, 1964;Den Otter et al, 1978;Kaissling et al, 1989;Pophof and van der Goes van Naters, 2002;Party et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, Plettner and coworkers have made great contributions to our understanding of olfaction in this species, in particular concerning the structure and function of its pheromone binding proteins (Kowcun et al, 2001;Honson et al, 2003;Honson and Plettner, 2006;Plettner and Gries, 2010;Gong and Plettner, 2011;Yu and Plettner, 2013). Recently, the L. dispar olfactory co-receptor (ORCO), a crucial component of olfactory receptor complexes, has been identified (Vosshall and Hansson, 2011;Lin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%